AN INVESTIGATION OF TOOTH LOSS IN GERIATRIC PATIENTS: A CROSS-SECTIONAL STUDY - Graziela Pardini; Anna Thereza Thomé Leão; Daniela Cia Penoni (Portal de Periódicos da Marinha do Brasil, 2019)
In order to provide a profile of the elderly people assisted by the Naval Dental Center (Odontoclínica Central da Marinha), it was performed an epidemiological survey seeking to outline the oral conditions and reported changes in eating habits in this population. A cross-sectional study aimed to describe the prevalence of edentulism and functional dentition in a population of 675 elderly aged more than 60. The impact of functional dentition (FD) on quality of life of these people was assessed, and the association of FD with changes in eating habits was evaluated. The following variables were collected: number of full and partials removable dentures user, number of implants and natural teeth. The participants were inquired about changes on eating habits due to oral status. Data analysis has shown that the average number of natural teeth was 15.7 ± 7.9, 24.1 had severe dental loss, 64.0% did not present functional dentition and 23.5% reported changes in eating and chewing in the last 6 months. It was concluded that a large number of the elderly people evaluated presents several missing teeth which may negatively have impacted on their oral related quality of life.